2021
DOI: 10.5267/j.ac.2021.5.009
|View full text |Cite
|
Sign up to set email alerts
|

Detecting fraudulent financial statements in pharmaceutical companies: Fraud pentagon theory perspective

Abstract: A fraudulent financial statement is an issue that continues to be discussed as a form of deviation from corporate governance. Covid-19 pandemic has also demanded management to uphold the company's performance to have a good public image. Thus, the present study sets out to scrutinize the fraud pentagon theory on fraudulent financial statements. Each element is not able to be tested directly. However, there are proxies. The pressure element is proxied as a personal financial need. The opportunity is becoming th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 1 publication
1
8
1
10
Order By: Relevance
“…Article 105 paragraph (1) states that the Board of Directors and the Board of Commissioners can be dismissed based on the General Meeting of Shareholders' decision (by stating the reasons). The result of this study is contrary to the results of studies carried out by Agrawal et al (1999), andAriyanto et al (2021) stated that detected companies suspected of fraud have a high turnover among directors. Third, for collusion, companies that have a project cooperation with the government were likely to commit an illegal act (GOVTPROJECT = 0.185) compared to those that do not (GOVTPROJECT = 0.181).…”
Section: Resultscontrasting
confidence: 99%
“…Article 105 paragraph (1) states that the Board of Directors and the Board of Commissioners can be dismissed based on the General Meeting of Shareholders' decision (by stating the reasons). The result of this study is contrary to the results of studies carried out by Agrawal et al (1999), andAriyanto et al (2021) stated that detected companies suspected of fraud have a high turnover among directors. Third, for collusion, companies that have a project cooperation with the government were likely to commit an illegal act (GOVTPROJECT = 0.185) compared to those that do not (GOVTPROJECT = 0.181).…”
Section: Resultscontrasting
confidence: 99%
“…The research of [21] revealed that audit failure increased due to the change of auditors in the company. Study [18,20,37,38] shows that clients can use the auditor switching mechanism to reduce the prospect of detecting fraudulent acts in the company's financial reporting. Auditor switching is the leading indicator of companies committing fraud that will harm stakeholders in the long term.…”
Section: Research Findingsmentioning
confidence: 99%
“…Semakin besar proporsi kepemilikan saham manajemen pada perusahaan, maka manajemen cenderung berusaha lebih giat untuk kepentingan pemegang saham yang tidak lain adalah dirinya sendiri (Ariyanto et al, 2021) dan (Mardianto & Tiono, 2019). Kepemilikan saham manajemen akan membantu penyatuan kepentingan manajer dan pemegang saham, sehingga manajer ikut merasakan secara langsung manfaat dari keputusan yang diambil dan ikut pula menanggung kerugian sebagai konsekuensi dari pengambilan keputusannya.…”
Section: Pendahuluanunclassified